Impact of high hydrostatic pressure on the stability of lytic bacteriophages cocktail Salmonelex™ towards potential application on Salmonella inactivation. (November 2021) - Maciel, Cláudia; Campos, Ana; Komora, Norton; Pinto, Carlos A.; Fernandes, Rui; Saraiva, Jorge A.; Teixeira, Paula
Abstract: This work consisted in the first comprehensive study in which the potential to exploit the Salmonella lytic bacteriophages cocktail, Salmonelex™, in association with high hydrostatic pressure (HHP) towards potential application in egg matrices decontamination was evaluated. The impact of HHP (200–600 MPa) on the bacteriophages' viability pointed out a stability in the range of 200–400 MPa. From 400 MPa onwards, the inactivation was potentiated by an increase in the pressure magnitude, being matrix dependent. Salmonelex™ possessed a prominent baroresistance, requiring 600 MPa to completely lose its infectivity. Egg yolk presented the highest baroprotective effect, followed by whole egg and egg white. Transmission electron microscopy unveiled that 500 and 600 MPa elicited a detrimental impact on the bacteriophages' structural integrity. It was noteworthy the barotolerance (200–300 MPa) of Salmonelex™, previously exposed to different pH conditions (5.0–9.0), which proved not to undermine its infectivity. Regarding the influence of ovalbumin, lysozyme, l -α-phosphatidylcholine, palmitic and oleic acids on the mild HHP-induced inactivation of Salmonelex™, a baroprotective effect was observed, particularly conferred by those compounds comprising egg yolk. The promising results highlighted the feasibility of utilizing Salmonelex™ as an adjuvant to mild HHP processing of egg matrices. Highlights: Salmonelex™ notable baroresistance – 600 MPa to completely lose its infectivity. Egg matrices conferred a baroprotective effect up to 500 MPa, particularly egg yolk. pH values (5–9) and egg compounds did not hinder phage infectivity at mild HHP. Structural damages only observed at 500/600 MPa, more notoriously in S16 phage. Feasibility of Salmonelex™ as an adjuvant to mild HHP processing of egg matrices.